In Vitro Quality Test Of The Combination Of Kefir Milk Compound, Sweet Star Fruit Extract (Averrhoa Carambola L.) And Red Ginger - Kartika Arum Wardani; Dara Pranidya Tilarso; Afidatul Muadifah; Choirul Huda (Sean Institute, 2023)
Milk kefir is fermented milk produced by the activity of Lactic Acid Bacteria (LAB), yeast and acetic acid bacteria. Kefir milk contains many nutrients and properties, including immunomodulators, antibiotics, antioxidants and is rich in probiotics when compared to yogurt. Kefir milk from goats has more benefits than those from cow's milk, but it is still rarely in demand by the public because of its pungent aroma and taste. Star fruit is also known to have properties as an antibacterial, natural antioxidant and natural sucrose. Red ginger has also been widely recognized as a spice that has many properties as antibacterial, antioxidant, anti-inflammatory, and antiviral. In this study, researchers wanted to know the quality of the combination of Kefir milk with sweet star fruit juice and red ginger extract. The research will be carried out from February to May 2021. The kefir milk test includes bacteriological and physicochemical tests. The research design used a completely randomized design centered on one factor, namely the concentration of red ginger extract (0% control concentration, 4.5%, 6%, 7.5%). With Replica 3 times. Physicochemical tests are total acidity test, Vitamine c test and viscosity test. The results of the study showed that kefir fermented goat milk with the addition of star fruit juice and ginger juice was good for consumption, namely in treatment group 1 (containing 20% ​​star fruit juice and 4.5% red ginger juice).